Primary cutaneous CD8+ small/medium‐sized pleomorphic T‐cell lymphoma, ear‐type: a unique cutaneous T‐cell lymphoma with a favourable prognosis - Géraud, Cyrill; Goerdt, Sergij; Klemke, Claus-Detlev (British journal of dermatology, 2011)
Madam, Compared with CD4+ primary cutaneous T‐cell lymphomas (CTCLs), CD8+ CTCLs occur infrequently. Among CD8+ CTCLs, CD8+ variants of CD4+ CTCL predominate; these display clinical features and prognosis similar to their CD4+ counterparts. According to the World Health Organization (WHO)-European Organisation for Research and Treatment of Cancer (EORTC) classification for cutaneous lymphomas, CD8+ variants of CD4+ CTCL occur in mycosis fungoides and its variant pagetoid reticulosis, Sézary syndrome (SS), CD30+ lymphoproliferative disorders, subcutaneous panniculitis‐like T‐cell lymphoma and nasal‐type natural killer/T‐cell lymphoma.1 Among the provisional entities in the WHO-EORTC classification, primary cutaneous aggressive epidermotropic CD8+ cytotoxic T‐cell lymphoma is defined by CD8 expression and is almost invariably associated with a fatal clinical outcome. In contrast, the provisional entity of small/medium‐sized pleomorphic CTCL was defined by the expression of CD4 to exclude the few CD8 cases that could not be lumped together by clinical presentation, histomorphology and course of disease.2 Recently, several groups have reported on an indolent CD8+ lymphoid proliferation on the ear with highly characteristic clinical and pathological features in a total of 10 patients.3-6 Here we describe another patient with this condition and suggest classifying this novel entity as primary cutaneous CD8+ small/medium‐sized pleomorphic T‐cell lymphoma, ear‐type.